Implementasi Metode Cycle Counting sebagai Upaya Peningkatan Akurasi Persediaan: Studi Kualitatif di PT Excelitas Technologies Batam Kepulauan Riau - Cut Mutia Sari; Wahyudiyono (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2025)
Accurate inventory management is crucial for manufacturing companies to sustain operations and customer loyalty. Inaccuracy of inventory data leads to issues such as overstocking, stockouts, and increased operational costs. This scientific article focuses on the implementation of cycle counting method as part of efforts to improve inventory accuracy in the company. Methods used in the implementation of cycle counting at PT Excelitas Technologies Batam is ABC analysis. The subject of this research is the employees of warehouse and finance department, while the object of this research is the implementation of cycle counting method as part of efforts to improve inventory accuracy: qualitative study at PT Excelitas Technologies Batam Riau Islands. The writing method used is descriptive narrative, using data collection techniques through observation in this research uses a rating scale, interviews, documentation, and literature study. The results of this research showed that the implementation of cycle counting periodically can improve the accuracy of inventory data, reduce stock variances, and minimize operational risks and costs. However, there were challenges in terms of limited human resources and technical issues in the implementation. Overall, cycle counting is proven effective in improving inventory management efficiency and serves as a reference for other companies with similar problems.